BLACK CHOIPAN BASED ON BLACK RICE FLOUR AS AN ALTERNATIVE SNACK FOR DIABETES MELLITUS - Sri Palupi, Utari Puspa Raissa (Prosiding Pendidikan Teknik Boga Busana, 2020)
Changes in lifestyle that occur today, affect eating habits which is not good. Poor eating habits can cause many kinds of degenerative diseases, one of which is diabetes mellitus. One strategy to control blood glucose levels is to regulate a healthy diet. The purpose of this research are: 1) to innovating traditional snack products that are suitable for people with diabetes mellitus who can be accepted and favored by the public in the making of Black Choi Pan based on black rice flour; 2) to know the nutritional value contained in Black Choi Pan products; 3) to know the level of acceptance of Black Choi Pan products. In this study using R & D experiments with a series of 4D steps (Determine, Design, Develop, Disseminate). The conclusion of this study are: 1) The Black Choi Pan product is better or close to the reference product; 2) Black Choi Pan products are very favored with the public; 3) Black Choi Pan products can be accepted by the public and become an alternative snack for people with diabetes mellitus. Key Words: black rice flour, snacks, functional food, diabetes mellitus, healthy snacks.